DAMPAK RELOKASI PEDAGANG KAKI LIMA ALUN-ALUN JOMBANG: (STUDI KASUS PEDAGANG KAKI LIMA DI JALAN DR. SOETOMO DAN JALAN KUSUMA BANGSA) - Lailatus Sa’adah; Andi Wicoro (Institut Teknologi dan Bisnis Dewantara, 2022)
The formulation of the problem in this study is, what is the impact felt by street vendors in the city of Jombang, especially street vendors in the square who have been relocated to Jalan Dr. Soetomo and Jalan Kusuma Bangsa, especially in terms of income. The purpose of this study was to find out how the impact of relocation for street vendors on income before and after relocation. The type used in this study is a qualitative method, the data collection techniques used are observation and interviews. The research sample is the street vendors on Dr. Street. Soetomo and Jalan Kusuma Bangsa, as many as 85 respondents. The results of this study indicate, the street vendors are all traders who were previously in the City Square. They have been selling for almost 10-20 years. After the relocation the traders began to adjust to the new place. There is a significant increase with the relocation of new places. There was an increase in sales followed by a nearly 40% increase in revenue from the previous year. The new selling place feels comfortable but cramped so that buyers can't stay longer when buying. Public MCK facilities are not provided and there are several other facilities that have not been considered by the Jombang City government.